Using antibiotic cement nail with multiple screws fixation as a single-stage salvage procedure for patient with infected tibiotalocalcaneal arthrodesis: A case report. (28th January 2020) - Chiu, Yen-Chun; Chen, I-Chien; Yang, Shih-Chieh; Kuo, Shyh-Ming; Kao, Yu-Hsien; Jou, I-Ming; Tu, Yuan-Kun
Tibiotalocalcaneal (TTC) arthrodesis with retrograde nail is a widely used treatment option for severe ankle arthropathy. With inherent biomechanical benefits in axial loading and strong bending stiffness, high union rate and good clinical outcomes have been reported in the literature. However, some undesired complications, such as osteomyelitis or implant failure, can develop after this procedure. Herein, we report the case of an 86-year-old man with right ankle osteomyelitis after TTC arthrodesis with retrograde nail. After removing the previous implants and extensive debridement, we used an antibiotic cement nail with multiple screws fixation as a salvage procedure in the same operation. The patient fully recovered without further surgical treatment.